Low temperature atomic hydrogen annealing of InGaAs MOSFETs. (15th March 2023) - Olausson, Patrik; Yadav, Rohit; Timm, Rainer; Lind, Erik
Abstract: Recent work showing a strong quality improvement of the Si/SiO2 material system by low temperature atomic hydrogen annealing (AHA), and the fact that III–V semiconductors outperform Si in many applications makes the investigation of AHA on III–V/high-k interfaces to a very interesting topic. In this work, the potential of AHA as a low temperature annealing treatment of InGaAs metal–oxide–semiconductor field-effect transistors is presented and compared to conventional annealing in a rapid thermal process (RTP) system using forming gas. It is found that post metal annealing in atomic hydrogen greatly enhances the quality of the metal–oxide–semiconductor structure in terms of effective mobility, minimum subthreshold swing, and reliability. The device performance is comparable to RTP annealing but can be performed at a lower temperature, which opens up for integration of more temperature-sensitive materials in the device stack.